Potentiality of Anthropophily to Enhance Nut Production in Cashew (Anacardium occidentale L.) - Kartik Kandar; Ujjwal Layek; Prakash Karmakar (Journal of Nuts)
Cashew nuts are highly demandable due to their nutritional value and utility. However, yield is below the optimum level. Several strategies were deployed to overcome its low productivity, like artificial hybridization, hormone treatment and bee management. Here, for the first time, we assessed the impact of vitamin (e.g., folic acid) treatment and anthropophily pollination on cashew yield. We sprayed vitamins started before the blooming period and continued through the flowering period; recorded flowering patterns; performed hand-pollination; recorded fruit set and fruit quality parameters for different systems at the Vidyasagar University campus (in the Paschim Medinipur district, West Bengal, India), during 2021–2023. Vitamin treatment significantly increased the number of flowers (both hermaphrodite and male flowers) development. Anthropophily pollination enhanced fruit set and nut quality (e.g., weight, length and breadth). Combined with vitamin treatment and anthropophily, it increases nut yield approximately five times compared to a non-manipulated system. While an additional cost is needed for human pollinators, the benefit-to-cost ratio in anthropophily pollination was high (i.e., 1.84: 1). Therefore, non-traditional human pollinators (i.e. anthropophily pollination) in addition to growth promoters (e.g., vitamins) utilization will be an effective strategy to increase the nut yield of cashew trees.